Shaping tomorrow’s dentists: a multi-institutional survey of undergraduate dental students’ perceptions towards interprofessional education - Sim, Galvin Siang Lin; Yook, Shiang Ng; Hashim, Hasnah; Chan, Choong Foong; Yahya, Noor Azlin; Muhamad Halil, Mohd Haikal; Ahmad, Mas Suryalis (BioMed Central Ltd, Springer Nature, 2024)
Background Interprofessional education (IPE) is essential to foster collaboration among healthcare professionals for holistic patient care. However, Malaysian dental education remains discipline-centric, hindering multidisciplinary learning approaches. Hence, this study aimed to explore Malaysian undergraduate dental students’ perceptions of IPE. Methods The present cross-sectional study employed convenience sampling to survey undergraduate dental students from four Malaysian institutions using a modified questionnaire with 20 close-ended and 2 open-ended questions. The questionnaire covered three domains (effectiveness, preference, importance) to assess students’ perceptions using a five-point Likert scale. Psychometric validation was performed to assure validity and reliability of the modified questionnaire. Quantitative analysis (descriptive and inferential statistics), and qualitative analysis (content analysis) were subsequently performed. Results 397 students responded, and positive perceptions were generally noted with mean scores ranging from 4.13 to 4.35 across all domains. Questions 2 and 3, assessing the improvement in understanding the roles and responsibilities, and communication among healthcare professionals, received the highest mean scores. Meanwhile, Question 15 concerning the incorporation of IPE into educational goals received the lowest mean score. Regression analysis identified gender and clinical phase as significant factors, with females and preclinical students exhibiting more favourable perceptions. Motivators for IPE included a keen interest in diverse perspectives and recognising the importance of teamwork, while barriers encompassed tightly packed schedules, lack of understanding about IPE, misconceptions regarding dental education, and students’ nervousness and fear of participation. Conclusion This study produced a valid and reliable instrument to measure undergraduate dental students’ perceptions towards IPE. Strategic planning, such as overcoming logistical challenges, improving awareness, and creating a supportive learning environment are crucial for successful IPE integration into existing curricula, especially in resource-constrained developing countries like Malaysia.